Idetifikasi Keterserapan Lulusan Jurusan Administrasi Bisnis Politeknik Negeri Samarinda - Andi Syarifuddin; Heldina Pristanti; Johan Lucas (Politeknik Negeri Samarinda, 2020)
The identification of Business Administration graduates absorption is one of the types of policy research that leads to the process of finding data and facts about the phenomenon of the absorption that most of graduates that are not maximized in accordance with their scientific fields with several phenomena lead to it. Based on the results of tracer studies of alumni majoring at Business Administration department in 2019 who have worked in various types of industries in East Kalimantan have shown a pretty good compared to the several years before were about 74% of alumni absorbed in various industry sectors and the rest worked in government agencies and entrepreneurship reaches (10%). The determine of the level of uptake the graduates in industry in accordance with the field of science, is largely determined by the availability of resources and have competencies that are in accordance with the level of skill requirements of each job related to administration and offices.